The Effects of FOMO on Investment Behavior in the Stock Market - Idris, Hariany (Golden Ratio of Data in Summary, 2024)
This study explores the impact of Fear of Missing Out (FOMO) on stock market investment behavior, focusing on how psychological and emotional factors influence investors' decision-making processes. The primary objective of the research is to investigate the relationship between FOMO and key behavioral trends, such as overtrading, speculative investing, and the formation of asset bubbles. A qualitative research approach was employed, utilizing a literature review of existing studies on behavioral finance, FOMO, and stock market dynamics. The findings indicate that FOMO significantly affects investors by amplifying emotional reactions to market trends, leading to irrational decisions that prioritize short-term gains over long-term financial stability. Social media and technology play a critical role in amplifying FOMO, creating herd behavior that contributes to market volatility and speculative bubbles, as seen in phenomena like "meme stocks." The study also reveals that younger investors are more susceptible to FOMO, largely due to their reliance on social media for investment advice. The results suggest that enhancing financial literacy and promoting disciplined, long-term investment strategies are essential for mitigating the negative effects of FOMO. Regulatory interventions targeting misinformation on digital platforms may also help reduce the prevalence of FOMO-driven investment behavior. Future research should further investigate the psychological mechanisms behind FOMO and explore the long-term sustainability of FOMO-driven market practices.